Religiosity and Interfaith Tolerance Among Students in Indonesian Islamic and General Junior Secondary Schools - Rahmat, Munawar; Supriadi, Udin; Fakhruddin, Agus; Surahman, Cucu; Taufiq Abdillah, Hilman; Nurjanah, Nunuy (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
Religious education plays a critical role in shaping both personal faith and interreligious harmony among students. This study investigates the levels of religiosity and religious tolerance among students attending Madrasah Tsanawiyah (MTs) and general junior secondary schools (SMP) in Indonesia. Employing a descriptive-quantitative research design, data were collected from 400 students—200 from MTs and 200 from SMP in West Java—using two validated questionnaires measuring religiosity and religious tolerance, each comprising 24 items. The findings reveal no significant difference in religiosity between MTs and SMP students, with the majority in both groups scoring high in religiosity (71% and 69%, respectively). However, a significant difference was observed in religious tolerance, with SMP students demonstrating higher tolerance levels (60.5%) compared to MTs students, who mostly showed lower tolerance (67.5%) (t = 7.649, p < .01). Additionally, while no significant correlation was found between religiosity and religious tolerance among MTs students (r = .055, p > .05), a moderate positive correlation was found among SMP students (r = .589, p < .01). These findings suggest that school type influences the development of religious attitudes, with general schools being more effective in fostering both religiosity and tolerance. The study underscores the need for further investigation into the pedagogical approaches used in SMP that successfully promote religious tolerance. It also calls for the development of religious education models in MTs that integrate tolerance-building strategies without compromising religious commitment.